Program Pengabdian Masyarakat Pengembangan Desa Wisata Makam Pangeran Benowo Di Desa Wonomerto Jombang - Fani Khoirotunnisa; Safina Najah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The strategy for developing Prince Benowo's tomb tourism in Wonosalam District, Jombang has become the focus of discussion. One strategy that stands out is the use of social media platforms such as YouTube and other platforms. In this context, interesting and informative video content, official YouTube channel, collaboration with local YouTubers or influencers, live streaming, and social media-based campaigns can be used to promote the tomb. In addition, other strategies include improving infrastructure, environmental management, providing adequate facilities and information, developing educational and cultural programs, as well as involving local communities and partnerships with related parties. Implementation of this strategy aims to create a good tourist experience, boost the local economy, and strengthen the cultural and historical identity of the village. Periodic evaluation and monitoring is required to ensure the successful implementation of the strategy and improvements where necessary. Thus, it is hoped that Prince Benowo's tomb tour will become an attractive, sustainable tourist destination, and provide benefits to the local community.